Ten Thousand Voices on Marine Climate Change in Europe: Different Perceptions among Demographic Groups and Nationalities - Buckley, Paul J.; Pinnegar, John K.; Painting, Suzanne J.; Terry, Geraldine; Chilvers, Jason; Lorenzoni, Irene; Gelcich, Stefan; Duarte, Carlos M. (Frontiers in Marine Science, 2017)
Over the past few decades, substantial funding has been directed towards improving scientific understanding and management of impacts of climate change in the marine environment. Following concerns that the key messages from these studies were not reaching the public, a comprehensive opinion poll of 10,000 European citizens in 10 countries was conducted to establish levels of awareness, concern, and trust among different demographic groups (by age, gender, proximity to the coast) and nationalities. Citizens exhibited varying levels of self-declared ‘informedness’ and concern. Citizens from Germany, Italy and Spain claimed to be the most informed on marine climate change issues; those from Czech Republic, Netherlands and Estonia claimed to be least informed. Respondents were least aware of ocean acidification and most aware of melting sea ice, pollution and overfishing. Citizens of Italy suggested that they were generally most concerned about marine climate change issues. Respondents from coastal areas claimed to be both more informed and more concerned than those living inland, as did females and older age groups (54-64 years). European citizens obtain information about climate change in the seas and ocean from different sources, particularly television and the internet. Trust in the various media sources varies among countries and demographic groups. Television is trusted most in Estonia, Germany and Ireland and least in France. The internet is trusted most in Italy, Czech Republic and Estonia, but least in France and the United Kingdom. 18-24 year olds are the biggest users of the internet, but trust this source less than older age groups. Academic scientists or those working for environmental NGOs are trusted more than scientists working for government or industry. Citizens from France are more trusting of industry than any other country polled. In terms of policy actions, most respondents highlighted mitigation measures as opposed to local-scale adaptation. Younger participants prioritised actions associated with reducing carbon emissions, whereas older age groups prioritised improving coastal defences. Successful adaptation to the impacts of climate change requires public engagement and support for policy decisions, and the use of different approaches to take account of differences among demographic groups and nationalities.